The Effect of Excess Carrier on a Semiconducting Semi-Infinite Medium Subject to a Normal Force by Means of Green and Naghdi Approach - Abouelregal, Ahmed E.; Sedighi, Hamid M.; Shirazi, Ali H. (SILICON, 2022)
For engineers and physicists, it is important to investigate the excitement of thermoelastic vibrations by photothermal effects since they are used in many fields. For this purpose, the photo-thermoelastic waves throughout the photothermal process for a semiconducting half-space have been investigated in this work. In contrast to many scientists who ignore the coupling effects between plasma and thermoelasticity, the influences of thermoelastic, carrier recombination and electronic elastic deformations on the semiconductor solids have been studied here. One of the thermoelastic theories which is appropriate for the limited speeds of heat waves has been considered. To solve the non-dimensional system resulting from generalized thermal elasticity theory without dissipating energy, coupled plasma, elastic wave and thermal wave equations, the normal mode technique has been applied. The amplitude expression for the field variables have been derived and graphically displayed. The numerical results have been verified and the influence of various factors has been also studied. In addition, several special cases of interest have been deduced. The analysis showed that the effective parameters have important effects on the physical fields by applying the presented model.